Protective role of ethyl pyruvate in spinal cord injury by inhibiting the high mobility group box-1/toll-like receptor4/nuclear factor-kappa B signaling pathway - Ruihua Fan; Ruihua Fan; Lvxia Wang; Lvxia Wang; Benson O. A. Botchway; Yong Zhang; Xuehong Liu; Xuehong Liu (Frontiers in Molecular Neuroscience, 2022)
Spinal cord injury (SCI) is a high incident rate of central nervous system disease that usually causes paralysis below the injured level. The occurrence of chronic inflammation with the axonal regeneration difficulties are the underlying barriers for the recovery of SCI patients. Current studies have paid attention to controlling the instigative and developmental process of neuro-inflammation. Ethyl pyruvate, as a derivative of pyruvate, has strong anti-inflammatory and neuroprotective functions. Herein, we reviewed the recent studies of ethyl pyruvate and high mobility group box-1 (HMGB1). We think HMGB1 that is one of the main nuclear protein mediators to cause an inflammatory response. This protein induces astrocytic activation, and promotes glial scar formation. Interestingly, ethyl pyruvate has potent inhibitory effects on HMGB1 protein, as it inhibits chronic inflammatory response by modulating the HMGB1/TLR4/NF-κB signaling pathway. This paper discusses the potential mechanism of ethyl pyruvate in inhibiting chronic inflammation after SCI. Ethyl pyruvate can be a prospective therapeutic agent for SCI.